The Social Construction of Yasinan in the Form of Social Identity “a Case Study in Ketapangkuning Village, Ngusikan Subdisctrict, Jombang Regency” - Widia Dwi Rahmawati; Agus Mahfudz Fauzi (LPPM IAIN Parepare, 2021)
Tradition becomes an important part that is closely related to people's lives. The existence of tradition is often motivated by many things, one of which is religion. In Javanese society, the religious element enters almost all traditions carried out. Yasinan tradition is a manifestation of the melting of Islamic religious values in society. Until now Yasinan Tradition still continues to undergo the regeneration process. However, as the era of this tradition has grown, the value shift is due to social construction. This condition also occurs in yasinan tradition carried out by the people of Ketapangkuning Village. Currently, Yasinan Tradition is only used as a medium for obtaining wealth alone. Thus, in its implementation has indirectly formed a social identity of a particular group. The purpose of this research is to see how the construction of Yasinan Tradition in the formation of social identity of local villagers. This research is included in qualitative research type. The method used in this study is social construction. The results showed that there is a shift in value in yasinan tradition conducted by the people of Ketapangkuning Village. Yasinan tradition becomes a medium in shaping the social identity of the local community. The formation of social identity is demonstrated through the 'arisan' activities carried out in the tradition.